Drug Discovery in Pancreatic Cancer Models and Techniques - Han, Haiyong.; Grippo, Paul. (Springer New York, 2010)
Over the past two decades, tremendous advances have been made in the field of cancer drug discovery, particularly in the area of molecular and genetic models and technologies, many of which have been or are beginning to be applied to the drug discovery process for pancreatic cancer. Drug Discovery in Pancreatic Cancer: Models and Techniques offers the latest development in the application of those models and technologies in pancreatic cancer. The authors include experts in their perspective field of research including basic scientists as well as clinicians who work on the frontline in the war against pancreatic cancer and have first-hand experience employing these cutting-edge tools and techniques. The book progresses logically from modeling systems to genomic profiling, proteomic analysis, and pharmacodynamic assays. It features: " Up-to-date survey of many cell lines and animal models of pancreatic cancer and their applications in drug discovery. " Application of fluorescent mouse models in pancreatic cancer drug discovery. " Utility of cutting-edge genomics, proteomics, epigenomics, and glycomics methodologies for molecular target identification and validation. " Discussion of microRNA profiling and high throughput RNAi screening for pancreatic cancer drug discovery. " Broad screening technologies for proteins and nucleic acids using tissue microarrays and CGH arrays. " Development of pharmacodynamic endpoint assays for targeted therapeutics. Comprehensive and practical Drug Discovery in Pancreatic Cancer: Models and Techniques offers both basic and clinical scientists who are interested in pancreatic cancer an up-to-date review and assessment of models and technologies being applied in drug discovery for pancreatic cancer. The true premise of this book is to provide a guide for drug discovery and evaluation, with consideration of various modeling systems and the methods for screening/profiling responses to these compounds. It is the Editors intent to stimulate new thought in this area of research as a means of generating much improved drug efficacy for greater survival and quality of life for patients battling pancreatic cancer.